United Chevrolet-Geo Toyota (Raton, NM Raton Range, 1992)
Article Spotlight on Raton's Family Owned Businesses and a brief history of how it started.
Newspaper article + photograph of the United Chevorlet-Geo Toyota Building
Master list item #: 44
File location is in the Raton file Cabinet
Keywords: Lackey, F. H; Lackey, John; Grubelnik, Harold; Lienke Motors -- Trinidad; Sunshine Motors; Triangle Chevrolet; United Chevrolet; Olsmobile Franchise; Buick; Cadillac; Toller Motors; Toyota; Pontiac; Circle Chevrolet-Geo Dealership -- Trinidad; United Chevrolet-Geo Toyota; Local Business; Family Owned Business; Dealerships; Automotive Shops; Vehicle Sales; Vehicle Repair; Raton, New Mexico; Trinidad, Colorado